Allopatric origin of sympatric whitefish morphs with insights on the genetic basis of their reproductive isolation. (15th July 2022) - Fang, Bohao; Momigliano, Paolo; Kahilainen, Kimmo K.; Merilä, Juha
Abstract: The European whitefish ( Coregonus lavaretus ) species complex is a classic example of recent adaptive radiation. Here, we examine a whitefish population introduced to northern Finnish Lake Tsahkal in the late 1960s, where three divergent morphs ( viz . littoral, pelagic, and profundal feeders) were found 10 generations after. Using demographic modeling based on genomic data, we show that whitefish morphs evolved during a phase of strict isolation, refuting a rapid sympatric divergence scenario. The lake is now an artificial hybrid zone between morphs originated in allopatry. Despite their current syntopy, clear genetic differentiation remains between two of the three morphs. Using admixture mapping, we identify five SNPs associated with gonad weight variation, a proxy for sexual maturity and spawning time. We suggest that ecological adaptations in spawning time evolved in allopatry are currently maintaining partial reproductive isolation in the absence of other barriers to gene flow.